A Practical Guide to Approaching Biased Agonism at G Protein Coupled Receptors - Gundry, Jaimee; Glenn, Rachel; Alagesan, Priya; Rajagopal, Sudarshan (Frontiers in Neuroscience, 2017)
Biased agonism, the ability of a receptor to differentially activate downstream signaling pathways depending on binding of a “biased” agonist compared to a “balanced” agonist, is a well-established paradigm for G protein-coupled receptor (GPCR) signaling. Biased agonists have the promise to act as smarter drugs by specifically targeting pathogenic or therapeutic signaling pathways while avoiding others that could lead to side effects. A number of biased agonists targeting a wide array of GPCRs have been described, primarily based on their signaling in pharmacologic assays. However, with the promised of biased agonists as novel therapeutics, comes the peril of not fully characterizing and understanding the activities of these compounds. Indeed, it is likely that some of the compounds that have been described as biased, may not be if quantitative approaches for bias assessment are used. Moreover, cell specific effects can result in “system bias” that cannot be accounted by current approach for quantifying ligand bias. Other confounding includes kinetic effects which can alter apparent bias and differential propagation of biological signal that results in different levels of amplification of reporters downstream of the same effector. Moreover, the effects of biased agonists frequently cannot be predicted from their pharmacologic profiles, and must be tested in the vivo physiological context. Thus, the development of biased agonists as drugs requires a detailed pharmacologic characterization, involving both qualitative and quantitative approaches, and a detailed physiologic characterization. With this understanding, we stand on the edge of a new era of smarter drugs that target GPCRs.